Fungal Infections of the Central Nervous System in the Seemingly Immunocompetent – common or unusual - Nawaz, Amina; Raza, Aun; Khan, Azizullah; Bakar, Muhammad Abu; Shafqat, Muhammad Ammar; Yousuf, Irfan; Sultan, Faisal (Infectious Diseases Journal of Pakistan, 2022)
Objective: To identify and describe characteristics of invasive Central Nervous System [CNS] fungal infections including their clinical presentation, diagnosis, treatment and outcome at our center. Methods: This is a retrospective study design using secondary data analysis. Medical records of patients with CNS fungal infections presenting during an eight-year period, from June 2011 to June 2018 were reviewed to determine patients’ baseline characteristics (age, gender, comorbidities), site of infection in brain, clinical presentation, imaging findings, medications used and response to treatment including mortality. Results: Twenty-one patients with invasive CNS fungal infection were identified and reviewed. A majority of patients were men (81%). The clinical presentation was variable and most patients presented with more than one feature. Headache was the commonest symptom and was seen in 67% of the patients. Response to treatment was better in patients with Aspergillosis (71.4%) as compared to other organisms (43%). The overall response rate of CNS fungal infections was 62%. Overall mortality in these patients was 24%. Voriconazole is better tolerated while Amphotericin B deoxycholate use was associated with expected kidney injury. Surgical excision at any time during the treatment was associated with better response. Conclusion: The results of present study show that CNS fungal infections cause significant mortality. The index of suspicion should be high even in immunocompetent patients presenting with headache, facial swelling or neurological involvement. Prompt and accurate diagnosis and early treatment should be instituted to avoid disease progression and mortality. There is a need for better tolerated drugs (Liposomal Amphotericin B and Posaconazole) to be available at low cost. Surgery should be considered as a treatment option wherever feasible. Key words: CNS – Central nervous system